CLEARING THE FIRST HURDLE: TIPS FOR GETTING AN "R&R" INVITATION. (11th November 2018) - Carr, D
Abstract: Publishing in competitive academic journals is a difficult feat, with only a fraction of submissions passing successfully through the first stage of the review process. This presentation will describe strategies for increasing the chances of receiving a "revise and resubmit" invitation (or the more rare and coveted "conditional acceptance") upon first submission. Topics to be covered include: (1) demonstrating the importance, significance, and novelty of your contribution; (2) striving for methodological rigor; (3) achieving a coherent narrative arc; 4) writing a manuscript that reviewers will enjoy reading; and (5) spreading the word about your research, once it's published.